Tingkat Penerapan Keselamatan, Kesehatan Kerja dan Lingkungan (K3l) Pada Proyek Konstruksi - Simanjuntak, Johan Oberlyn; Lumbangaol , Partahi; Simanjuntak, Salomo; Pasaribu, Humisar; Simanungkalit, Okto (Jurnal Visi Eksakta, 2022)
Increased development in various regions in Indonesia, especially in the city of Medan, makes many contactors compete with each other in implementing a project. Starting from the time, quality, and cost. However, there are still many contractors who ignore Occupational Safety, Health and Environment (K3L). This study aims to determine the level of application of Occupational Safety, Health and Environment (K3L) in construction projects. Occupational Health, Safety and Environment (K3L) is a program that aims to create a safe, healthy workplace. So that it can reduce the risk of work accidents and occupational diseases as low as possible on the project. The theory used in this study uses quantitative methods that tend to produce descriptive results. The sampling technique was carried out by observation and questionnaire. The instrument used comes from the Minister of Public Works Regulation No. 9 of 2008. This research was conducted on the Cinema Grand Jati Junction construction project located on Jln Perintis Kemerdekaan, Medan The results of the research on the level of application of Occupational Safety, Health, and Environment (K3L) for the Cinema Grand Jati Junction construction project on Jln Perintis Kemerdekaan, Medan amounted to 90.54%. The completeness of K3L facilities in the project was 86.7%.